Plan de marketing para la empresa “Mundo Ferretero” de la ciudad de Santo Domingo de los Tsáchilas - Morán Alpaz, Karina Alexandra (2015)
In research on "MARKETING PLAN FOR BUSINESS WORLD FERRETERO CITY OF SANTO DOMINGO TSÁCHILAS" was developed in the City of Santo Domingo, with the overall objective to develop a strategic marketing plan in order to improve economic and competitive development of the company as a marketing plan is an essential tool that allows and facilitates effective marketing of any product or service. It is very risky to try a business succeed without having developed a marketing plan. This research work includes: Summary, which corresponds to a summary of the relevant parts of the thesis; the Introduction, in this the importance of the subject under investigation, by which highlights have disclosed all the work done; Review of literature consists of citations containing theoretical contexts for marketing plan, including: concepts and importance of the most used items; Materials and Methods below detailing methods: deductive, inductive, descriptive techniques such as direct observation, interview, and survey procedures used in the investigation that led to collect the information necessary to determine facts and phenomena that occur in the business environment and to identify the key internal and external problems that affect the same. The results, disclosed internal and external analysis of the company World Ferretero, historical background, organizational structure etc., a SWOT analysis of the company is also performed, in which the internal factors were determined as are the Strengths and Weaknesses and external factors that are the threats and opportunities, then the matrix of criteria for high impact and valuation is done with their respective percentages. According to the analysis of the EFE and EFI matrices, it is determined that the factor weighted EFE is 2.40 which indicates that the company there is a predominance of threats on opportunities, ie can face the threats exploiting market opportunities. With respect to the weighted factor EFI, a value of 2.49 was obtained, which implies that the company has the same internal problems if the q can fight. Finally after the SWOT analysis, it is determined each of the strengths, weaknesses, opportunities and threats that the company and then determine Matrix High Impact strategic objectives for the company. Finally Conclusions, Recommendations of the research are: To the manager implement them and take corrective measures for your organization; Bibliography, is the part where you have to know the sources of information used in the development of this work and finally annexed the same q were used to collect all information necessary for the development of the marketing plan.